Partial privatization and intellectual capital: The moderating role of firm internationalization and regional development - Haobo Xie (PLoS ONE, 2026)
This study examines the impact of partial privatization on intellectual capital and investigates how corporate internationalization and regional development moderate this relationship. Using a sample of Chinese listed firms over the years of 2010–2023, this study employed Ordinary Least Squares (OLS) as the baseline regression. This study finds that partial privatization positively affects intellectual capital, thereby introducing opportunities about value creation within firms. Further investigations reveal that internationalization weakens the positive impact of partial privatization on intellectual capital, suggesting that exposure to international markets may heighten agency risks associated with a firm’s global expansion. Our findings also show that regional development strengthens this positive relationship, since firms located in developed regions are better positioned to capitalize on the benefits of partial privatization. To ensure the robustness of these findings, we also use two Generalized Method of Moments (GMM) and Propensity Score Matching (PSM) methods to ensure the consistency of the findings. Overall, the results carry significant policy implications, especially concerning the corporate efficiency outcomes of privatization in emerging markets such as China.